Standard Specification for High-Strength Carbon-Manganese Steel of Structural Quality (American Society of Testing Materials, 2009)
This specification covers carbon-manganese steel shapes, plates, and bars of structural quality for use in riveted, bolted, or welded construction of buildings and for general structural purposes.